THE IMPACT OF PRODUCER MARKETING STRATEGIES THROUGH E-COMMERCE ON UMKM IN THE PERSPECTIVE OF SHARIA ECONOMIC LAW - Dony Eko Prasetyo (Universitas Nurul Jadid, 2025)
The rise of e-commerce has revolutionized transaction patterns and marketing strategies in Indonesia. Its ease of access, extensive promotions, and operational efficiency provide significant advantages for large-scale producers in reaching consumers. However, this advancement poses serious challenges for Usaha Mikro, Kecil, dan Menengah (UMKM)that still operate traditionally. The imbalance in competitiveness, declining customer visits to offline markets, and threats to local economic sustainability emerge as key issues. This study adopts a qualitative approach through a literature review to analyze the impact of large producers’ marketing strategies via e-commerce from the perspective of Islamic economic law. Findings indicate that Sharia principles—such as justice, transparency, and social responsibility—demand ethical standards in competition, ensuring that digital marketing practices do not marginalize MSMEs. Therefore, regulatory and educational interventions from the government are necessary to promote inclusive digital transformation while maintaining economic balance through the application of Islamic values in online business practices.